Global perspectives on recruiting international students : challenges and opportunities - Shneikat, Belal; Cobanoglu, Cihan; Tanova, Cem (Emerald Publishing Limited, 2021)
Although many countries have created effective strategies to recruit more international students due to proven economic and social benefits, recruiting international students as a field of research lacks coherence. Filling this gap, this book provides a holistic and comprehensive overview of this emerging research area. Exploring the theoretical and practical aspects of recruiting international students, this edited collection considers the financial, administrative, legislative, socio-cultural and market related barriers to international recruitment. The chapters cover a broad range of topics such as the role of social media in recruiting international students, the impact of internal environment on the recruitment of international students and the internationalization of universities as a strategy for recruiting international students. Offering a wide-ranging snapshot of global policies on international student recruitment across Asia, Europe and North America, as well as a consideration of related issues such as student integration and cultural adjustments, the authors and editors equip readers interested in the theory and practice with a more sophisticated view of the field, empowering them to engage in further research and practical strategies.